2001
DOI: 10.1093/tropej/47.4.239
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hepatitis B, Hepatitis C and Human Immune Deficiency Virus Markers in Multi-transfused Patients

Abstract: All patients presenting with hereditary hemolytic anemia, (n = 143) over a period of 18 months were enrolled in a study to evaluate the prevalence of hepatitis B, hepatitis C and HIV in multi-transfused patients in Jordan, and to identify possible related risk factors. All patients were treated in the Thalassemia Unit at Princess Rahma Teaching Hospital. Relevant clinical data were collected. Blood specimens were taken from these patients and tested for HbsAg, HbsAb, hepatitis core IgMAb, hepatitis core IgGAb,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 0 publications
3
43
2
Order By: Relevance
“…The prevalence rate of seropositivity increases with the number of transfusions. 15 However, since no vaccine is so far available against hepatitis C, the only effective protective measure against this virus is provision of HCV negative blood for transfusion in thalassemia patients. 16 The aims of this study include to determine the prevalence of HCV and HBV seropositivity amongst multiple-transfused thalassemia major patients in our setup and to judge the effectiveness of our current screening system for detection of these viruses in donor blood samples prior to transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate of seropositivity increases with the number of transfusions. 15 However, since no vaccine is so far available against hepatitis C, the only effective protective measure against this virus is provision of HCV negative blood for transfusion in thalassemia patients. 16 The aims of this study include to determine the prevalence of HCV and HBV seropositivity amongst multiple-transfused thalassemia major patients in our setup and to judge the effectiveness of our current screening system for detection of these viruses in donor blood samples prior to transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…9 But the result of our observation is higher than that reported from other countries, where this ranged from 0.53% to 3.5%. 5 Studies conducted in early 1990s in India showed a much higher prevalence of HBsAg ranging from 22% to 45%. 10 The differences in the results may be due to various factors such as (1) the sensitivity of ELISA, (2) the absence of HBsAg during the window phase and the convalescent phase, (3) very low levels of viremia, (4) effectiveness of screening programmes of blood and (5) the immune status o f r e cipient of multiple transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our study, Alsheyyab et al reported 3.5% HBeAg and 22% anti-HBe positivity among Arabian children suffering from hereditary haemolytic anemia. 5 Positive HBeAg indicates that the virus replicates, encodes and infects liver cells when it remains highly infectious. 14 On the other hand anti-HBe antibody indicates seroconversion and appearance of anti-HBe is a strong evidence that the patient will recover.…”
Section: Discussionmentioning
confidence: 99%
“…5 Prevalence studies have found that common infections occurring in thalassemic patients are Hepatitis C (2.2%-44%), followed by Hepatitis B (1.2%-7.4%) and HIV (0%-9%). 6 There is a paucity of studies of prevalence of hepatitis C in multi -transfused thalassemic patients in this region, and thus we conducted this study.…”
Section: Introductionmentioning
confidence: 99%